Entrepreneurship Development Tendencies and Empirical Approach - Mura, Ladislav (IntechOpen, 2018)
In context of entrepreneurship, this book was motivated by a desire of a team of well-known authors. The book consists of 23 closely related thematic contributions, which fall into 4 separate sections: Interactions between Economy and Entrepreneurship; Innovation in Entrepreneurship and Economic Growth; Current Trends in Family Business, Social Entrepreneurship and Responsibility; and The Role of Human Resource Management, Education and Gender in Entrepreneurship. Authors-contributors have submitted the results of their recent research and presented essential findings about the decision-making process of entrepreneurs in order to maintain their businesses competitive. The reader can get an insight into the selection of the best scientific contributions that have been reviewed and ready for debate. Our piece of work, Entrepreneurship: Development Tendencies and Empirical Approach, has interdisciplinary features. This work by authors from different countries - Finland, Germany, Czech Republic, Slovakia, Italy, Spain, Turkey and Malaysia - is dedicated to readers providing up-to-date research data and background for further research as well as implementation techniques in business practice.